Self-supporting positive electrode material, positive electrode, preparation method of positive electrode and battery
The preparation of Na3.1Fe4[Fe(CN)6]3@GA composite material was solved by a two-step thermal reaction method, which solved the conductive ability and volume expansion problems of Prussian blue analog materials, and achieved the preparation of self-supported positive electrode materials and improved battery performance. .
Patent Information
- Application Number
- CN202411353514.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-17
AI Technical Summary
The existing Prussian blue analogue (PBA) materials have insufficient conductivity during the preparation process and inevitably volume expansion problems during the circulation process, resulting in poor battery capacity attenuation and circulation performance, and inconvenient application of powder materials.
The self-supporting positive electrode material was prepared by a two-step thermal reaction method. By using graphene oxide with sodium ions and ferricyano ions in hydrothermal reaction, Na3.1Fe4[Fe(CN)6]3@GA composite material was formed with three-dimensional Aerogel composite material with spatial network structure ensures the stability and conductivity of the material.
The preparation of self-supporting positive electrode material is realized, with flexible self-supporting properties, and can be directly pressed into the positive electrode of the battery, improving the electrochemical performance and cycling stability of the battery, avoiding the problems of battery capacity attenuation and poor cycling performance.
Smart Images

Figure CN119153658A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery material preparation, and in particular to a self-supporting positive electrode material, a positive electrode and a preparation method thereof, and a battery. Background Art
[0002] Prussian blue analogues (PBAs) have the characteristics of open skeleton structure, abundant redox active sites and high stability, low cost, high specific capacity, excellent rate performance, and great potential in the future. However, PBAs have problems such as insufficient conductivity and inevitable volume expansion during the cycle. Therefore, a PBA@GA composite material with an encapsulation structure was prepared. Compared with pure PBAs and GA electrode materials, the obtained composite material combines the advantages of GA's excellent conductivity and pure PBAs' high specific capacity. In addition, GA's excellent conductivity and three-dimensional network structure provide a large number of ion exchange channels, which effectively alleviate the agglomeration and volume expansion effect of PBAs particles during the cycle.
[0003] The existing positive electrode materials are mainly PBA@G composite materials (powder) obtained by wrapping Prussian blue with graphene. The powder material cannot be directly pressed into sheets as a positive electrode. It needs to be slurried with a binder and a conductive agent and then attached to the current collector as a coating to make the positive electrode. The application process is not convenient enough.
[0004] The prior art also discloses a coprecipitation method for preparing a PBA@GA composite material, the main steps of which are: dispersing graphene oxide in a solution, adding cyanide and a transition metal salt to the solution, reducing the graphene oxide in the solution system, and coprecipitating the cyanide and the transition metal salt, followed by drying to prepare the PBA@GA composite material. The inventors have found that the PBA nanomaterial prepared by this method may have defects and be amorphous, and may cause battery capacity decay and poor cycle performance when used as an electrode material.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a self-supporting positive electrode material, a self-supporting positive electrode material, a method for preparing a positive electrode, a positive electrode and a battery.
[0007] The present invention is achieved in that: In a first aspect, the present invention provides a method for preparing a self-supporting positive electrode material, comprising: The reaction slurry is placed in an environment of 65-75°C for reaction for 20-28 hours, and then the temperature is raised to 90-110°C for reaction for 2-3 hours to obtain a hydrogel, and the hydrogel is freeze-dried to obtain a self-supporting positive electrode material; The components of the reaction slurry include deionized water, graphene oxide, a reducing agent for reducing graphene oxide, and a 3.1 Fe 4 [Fe(CN) 6 ] 3 of ferrocyanide and sodium ions; Graphene oxide reacts with the target Na 3.1 Fe 4 [Fe(CN) 6 ] 3 The molar ratio is 1:0.9~1.1.
[0008] In an optional embodiment, the preparation method of the reaction slurry includes: Sodium ferrocyanide reducing agent, graphene oxide powder and deionized water were mixed and ultrasonically dispersed for 50 to 70 minutes.
[0009] In an optional embodiment, the reaction slurry also includes ethylene glycol, the volume ratio of deionized water to ethylene glycol is 0.8~1.2:1, and the volume ratio of graphene oxide powder to ethylene glycol is 1 mol:1.5~1.8L.
[0010] In an optional embodiment, the sodium ferrocyanide is Na 4 Fe(CN) 6 10H 2 O.
[0011] In an optional embodiment, the particle size of the graphene oxide powder is 50-500 nm.
[0012] In an optional embodiment, the reducing agent is selected from at least one of ethylenediamine and ascorbic acid.
[0013] In an optional embodiment, before freeze-drying the hydrogel, impurities are removed by washing the hydrogel alternately with deionized water and anhydrous ethanol for multiple times.
[0014] In a second aspect, the present invention provides a self-supporting positive electrode material, which is prepared by the preparation method of any one of the aforementioned embodiments.
[0015] In a third aspect, the present invention provides a method for preparing a positive electrode, comprising tableting the self-supporting positive electrode material according to the aforementioned embodiment.
[0016] In a fourth aspect, the present invention provides a positive electrode, which is prepared by the preparation method as described in the above embodiment.
[0017] In a fifth aspect, the present invention provides a battery comprising a positive electrode as described in the aforementioned embodiment.
[0018] The present invention has the following beneficial effects: The preparation method provided by the present invention comprises the following steps: hydrothermally reacting graphene oxide (GO) with a PBA precursor (sodium ions and ferrocyanide ions) and a reducing agent. During the hydrothermal reaction, the graphene oxide is reduced to form graphene aerogel (GA), and the sodium ions and ferrocyanide ions react to form Na 3.1 Fe 4 [Fe(CN) 6 ] 3 , get Na 3.1 Fe 4 [Fe(CN) 6 ] 3 @GA composite material, which has flexible self-supporting properties and can be directly pressed to serve as the positive electrode of the battery.
[0019] The preparation method provided by the present invention adopts two thermal reactions to prepare hydrogel, and then freeze-drying to prepare aerogel composite materials with a three-dimensional spatial network structure. In the first thermal reaction, the composite material is basically generated in the reaction system; in the second thermal reaction, the reaction products in the system condense into blocks, the volume is reduced, the density is increased, and the structural stability of the composite material is improved. The present invention can not only ensure the stability of the three-dimensional spatial structure of the composite material through the two-step thermal reaction method, but also ensure that the Na generated by the reaction 3.1 Fe 4 [Fe(CN) 6 ] 3 Nanomaterials are defect-free and amorphous, and their use as electrode materials will not cause battery capacity decay or poor cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 This is a photograph of the self-supporting positive electrode material prepared in Example 1; Figure 2 This is the SEM image of the self-supporting positive electrode material prepared in Example 1. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0023] The following is a self-supporting positive electrode material, a positive electrode and a preparation method thereof, and a battery provided in the embodiments of the present invention.
[0024] Explanation of terms used in this article: Prussian blue analogues (PBAs); Graphene aerogel (GA); Graphene hydrogel (GH); Graphene oxide (GO); Graphene (G).
[0025] The method for preparing a self-supporting positive electrode material provided by an embodiment of the present invention comprises: The reaction slurry is placed in an environment of 65-75°C for reaction for 20-28 hours, and then the temperature is raised to 90-110°C for reaction for 2-3 hours to obtain a hydrogel, and the hydrogel is freeze-dried to obtain a self-supporting positive electrode material; The components of the reaction slurry include deionized water, graphene oxide, a reducing agent for reducing graphene oxide, and a 3.1 Fe 4 [Fe(CN) 6 ] 3 of ferrocyanide and sodium ions; Graphene oxide reacts with the target Na 3.1 Fe 4 [Fe(CN) 6 ] 3 The molar ratio is 1:0.9~1.1.
[0026] In the preparation method of the self-supporting positive electrode material provided in the embodiment of the present invention, graphene oxide (GO) and PBA precursor (sodium ions and ferrocyanide ions) are subjected to hydrothermal reaction together with a reducing agent. During the hydrothermal reaction, graphene oxide is reduced to form graphene aerogel (GA), and sodium ions and ferrocyanide ions react to form Na 3.1 Fe 4 [Fe(CN) 6 ] 3 , get Na 3.1 Fe 4 [Fe(CN) 6 ] 3 @GA composite material, which can be directly pressed into positive electrode. This material has excellent conductivity and high specific capacity.
[0027] The preparation method provided by the present invention adopts two thermal reactions to prepare hydrogel, and then freeze-drying to prepare aerogel composite materials with a three-dimensional spatial network structure. In the first thermal reaction, the composite material is basically generated in the reaction system; in the second thermal reaction, the reaction products in the system condense into blocks, the volume is reduced, the density is increased, and the structural stability of the composite material is improved. The present invention can not only ensure the stability of the three-dimensional spatial structure of the composite material through the two-step thermal reaction method, but also ensure that the Na generated by the reaction 3.1 Fe 4 [Fe(CN) 6 ] 3 Nanomaterials are defect-free and amorphous, and their use as electrode materials will not cause battery capacity decay or poor cycle performance.
[0028] Optionally, the preparation method of the reaction slurry includes: Sodium ferrocyanide, reducing agent, graphene oxide powder and deionized water were mixed and ultrasonically dispersed for 50 to 70 minutes.
[0029] Optionally, the reaction slurry also includes ethylene glycol, the volume ratio of deionized water to ethylene glycol is 0.8-1.2:1, and the volume ratio of graphene oxide powder to ethylene glycol is 1 mol:1.5-1.8L.
[0030] Ethylene glycol added to the slurry can form hydrogen bonds and van der Waals forces with water, thereby increasing the molecular cross-linking of the hydrogel and improving the mechanical properties of the hydrogel; ethylene glycol can change the solubility and polarity of water, reduce the interaction between water molecules, and make water form smaller aggregates, thereby promoting the formation and stability of the gel; ethylene glycol can increase the consistency and viscosity of the hydrogel, reduce the crystal morphology, and reduce the deviation of the crystal fixed point, thereby improving the mechanical properties and stability of the hydrogel. Therefore, adding ethylene glycol to the slurry can promote the acquisition of Na+ with better structural stability. 3.1 Fe 4 [Fe(CN) 6 ] 3 @GA Composite materials with self-supporting properties.
[0031] Optionally, sodium ferrocyanide is Na 4 Fe(CN) 6 10H 2 O.
[0032] Optionally, the reducing agent is selected from at least one of ethylenediamine and ascorbic acid.
[0033] Optionally, the particle size of the graphene oxide powder is 50-500 nm. Graphene oxide powder in this particle size range can be more evenly dispersed in the slurry, ensuring that the graphene particles obtained after reduction are evenly distributed on the three-dimensional network structure.
[0034] Optionally, before freeze-drying the hydrogel, impurities are removed by washing the hydrogel alternately with deionized water and anhydrous ethanol for multiple times.
[0035] The self-supporting positive electrode material provided in the embodiment of the present invention is prepared by the preparation method provided in the embodiment of the present invention.
[0036] The self-supporting positive electrode material provided in the embodiment of the present invention is prepared by the preparation method provided in the embodiment of the present invention, so it can be directly made into a positive electrode sheet by pressing, and it has better electrochemical performance.
[0037] The method for preparing a positive electrode provided by an embodiment of the present invention comprises pressing the self-supporting positive electrode material provided by an embodiment of the present invention into sheets.
[0038] The positive electrode provided by the embodiment of the present invention is prepared by the preparation method provided by the embodiment of the present invention.
[0039] The battery provided by the embodiment of the present invention includes the positive electrode provided by the embodiment of the present invention.
[0040] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0041] Example 1 Weigh Na 4 Fe(CN) 6 10H 2 O (0.02 mol), ascorbic acid (0.04 mol) and graphene oxide powder (0.003 mol) were added to deionized water (5 mL) and ethylene glycol (5 mL) in a high-temperature autoclave, and the reaction slurry was obtained after ultrasonic treatment for 1 h; The reaction slurry was placed in a 70°C oven for reaction for 24 hours, heated to 100°C for further reaction for 2.5 hours, and then naturally cooled to room temperature; The reaction product was separated into solid and liquid, the solid was collected, and the product was washed several times with deionized water and anhydrous ethanol, and then placed in a freeze drying oven to dry overnight, and finally Na 3.1 Fe 4 [Fe(CN) 6 ] 3 @GA composite material, in which Na 3.1 Fe 4 [Fe(CN) 6 ] 3 The molar ratio of GA is 0.95:1.
[0042] Example 2 Weigh Na 4 Fe(CN) 6 10H 2O (0.019 mol), ascorbic acid (0.04 mol) and graphene oxide powder (0.003 mol) were added to deionized water (3.6 mL) and ethylene glycol (4.5 mL) in a high-temperature autoclave, and the reaction slurry was obtained after ultrasonic treatment for 50 min; The reaction slurry was placed in a 70°C oven for reaction for 24 hours, heated to 100°C for further reaction for 2.5 hours, and then naturally cooled to room temperature; The reaction product was separated into solid and liquid, the solid was collected, and the product was washed several times with deionized water and anhydrous ethanol, and then placed in a freeze drying oven to dry overnight, and finally Na 3.1 Fe 4 [Fe(CN) 6 ] 3 @GA composite material, in which Na 3.1 Fe 4 [Fe(CN) 6 ] 3 The molar ratio of GA is 0.9:1.
[0043] Example 3 Weigh Na 4 Fe(CN) 6 10H 2 O (0.023 mol), ascorbic acid (0.04 mol) and graphene oxide powder (0.003 mol) were added to deionized water (6.5 mL) and ethylene glycol (5.4 mL) in a high-temperature autoclave, and the reaction slurry was obtained after ultrasonic treatment for 60 min; The reaction slurry was placed in a 70°C oven for reaction for 24 hours, heated to 100°C for further reaction for 2.5 hours, and then naturally cooled to room temperature; The reaction product was separated into solid and liquid, the solid was collected, and the product was washed several times with deionized water and anhydrous ethanol, and then placed in a freeze drying oven to dry overnight, and finally Na 3.1 Fe 4 [Fe(CN) 6 ] 3 @GA composite material, in which Na 3.1 Fe 4 [Fe(CN) 6 ] 3 The molar ratio of GA is 1.1:1.
[0044] Example 4 This embodiment is basically the same as embodiment 1, except that the reaction slurry is placed in a 65° C. oven for reaction for 28 h, heated to 90° C. for further reaction for 3 h, and then naturally cooled to room temperature.
[0045] Example 5 This embodiment is basically the same as embodiment 1, except that the reaction slurry is placed in a 75° C. oven for reaction for 20 h, heated to 110° C. for further reaction for 2 h, and then naturally cooled to room temperature.
[0046] Comparative Example 1 This comparative example is basically the same as Example 1, except that the reaction slurry is placed in an oven at 70° C. for reaction for 27 hours and then naturally cooled to room temperature.
[0047] Comparative Example 2 This comparative example is basically the same as Example 1, except that the reaction slurry is placed in an oven at 100° C. for reaction for 27 hours and then naturally cooled to room temperature.
[0048] Comparative Example 3 This comparative example is basically the same as Example 5, except that the reaction slurry is placed in a 75° C. oven for reaction for 20 h, heated to 120° C. for further reaction for 2 h, and then naturally cooled to room temperature.
[0049] Comparative Example 4 This comparative example is basically the same as Example 1, and the parts not mentioned refer to Example 1, except that: The Na 3.1 Fe 4 [Fe(CN) 6 ] 3 @GA composite material. The specific method is as follows: 0.003 mol of graphene oxide powder was ultrasonically dispersed in 5 mL of deionized water to obtain dispersion A; 0.02 mol Na 4 Fe(CN) 6 10H 2 O is dissolved in dispersion A to obtain dispersion B; 0.04 mol ascorbic acid and 0.03 mol ferric chloride were added into 5 mL of deionized water and dissolved to obtain solution C; Dispersion B and solution C were mixed evenly and then allowed to stand for 48 hours to obtain a hydrogel; Add 5 mL of ethanol to the hydrogel, soak for 10 h and then pour it out, and repeat 5 times to obtain the alcohol gel.
[0050] The alcogel was freeze-dried.
[0051] Comparative Example 5 This comparative example is basically the same as Example 2, except that: reducing Na 4 Fe(CN) 6 10H 2 O dosage, prepared Na 3.1 Fe4 [Fe(CN) 6 ] 3 Na in @GA composites 3.1 Fe 4 [Fe(CN) 6 ] 3 The molar ratio of GA is 0.7:1.
[0052] Comparative Example 6 This comparative example is basically the same as Example 3, except that: increasing Na 4 Fe(CN) 6 10H 2 O dosage, prepared Na 3.1 Fe 4 [Fe(CN) 6 ] 3 Na in @GA composites 3.1 Fe 4 [Fe(CN) 6 ] 3 The molar ratio of GA is 1.3:1.
[0053] Experimental Example 1 The surface image and SEM image of the composite material obtained in Example 1 are taken. Figure 1 and Figure 2 shown.
[0054] from Figure 1 It can be seen that the composite material prepared in Example 1 of the present invention is a non-powdery structure. Figure 2 It can be seen that the prepared composite material has a three-dimensional spatial network structure.
[0055] Experimental Example 2 The Na 3.1 Fe 4 [Fe(CN) 6 ] 3 @GA composite material is pressed and cut into discs of certain specifications to serve as the self-supporting positive electrode of sodium ion battery; sodium sheet is cut into discs of certain specifications and assembled into button-type half-cell CR2032 in the glove box. The electrolyte is 1 mol / L NaClO 4 The solution solvent is DEC:EC=1:1Vol% and 5%FEC, and the diaphragm is a glass fiber diaphragm.
[0056] The electrochemical performance of the battery was tested on a charge and discharge test cabinet at room temperature. The test conditions were a voltage range of 2.0-4.0 V and a charge and discharge rate of 0.2-1C. The measured results are recorded in Table 1.
[0057] Table 1 Performance of batteries prepared in various embodiments and comparative examples
[0058] It can be seen from the data in Table 1 that the positive electrode material prepared in the embodiment of the present invention has better electrochemical performance after being made into a battery.
[0059] Comparing Example 1 with Comparative Example 1, the capacity, cycle and rate performance of Comparative Example 1 are significantly worse than those of Example 1; comparing Example 1 with Comparative Example 2, the cycle performance of Comparative Example 2 is significantly worse than that of Example 1. This shows that it is difficult to achieve the best performance of the prepared positive electrode material whether only the first heating at a slightly lower temperature or only the second heating at a slightly higher temperature is performed. The present invention adopts a two-step thermal reaction, which can better improve the electrochemical performance of the prepared positive electrode material.
[0060] Comparing Example 5 with Comparative Example 3, the rate performance of Comparative Example 3 is significantly worse, and the difference between Comparative Example 3 and Example 5 is that the temperature of the second step thermal reaction is increased, which indicates that the temperature of the second step thermal reaction should be within the range required by the present invention. If the temperature exceeds the temperature required by the present invention, the graphene-wrapped PBAs will be too dense, which will hinder the Na + Transmission, impedance increases and rate performance decreases.
[0061] Comparing Example 1 with Comparative Example 4, the capacity, cycle and rate performance of Comparative Example 4 are poor. Comparative Example 4 adopts the existing known coprecipitation method to prepare aerogel Na 3.1 Fe 4 [Fe(CN) 6 ] 3 @GA composite material. This shows that the positive electrode material prepared by the two-step thermal reaction preparation method provided by the present invention has better performance.
[0062] Comparing Comparative Example 5 with Example 2, the specific capacity of Comparative Example 5 is significantly worse, which indicates that the Na 3.1 Fe 4 [Fe(CN) 6 ] 3 The proportion should not be too small, otherwise it will affect the loading amount of the composite material on GA, resulting in a decrease in capacity performance; comparing Comparative Example 6 with Example 3, the rate and cyclability of Comparative Example 6 are significantly worse, which shows that the Na 3.1 Fe 4 [Fe(CN) 6 ] 3 The proportion should not be too high. 3.1 Fe 4 [Fe(CN) 6 ] 3 The ratio of GA to GA must be within the range of 0.9 to 1.1:1 as required by the present invention to ensure good electrochemical performance.
[0063] In summary, the preparation method provided by the present invention is to hydrothermally react graphene oxide (GO) with PBA precursor (sodium ions and ferrocyanide ions) and a reducing agent. During the hydrothermal reaction, graphene oxide is reduced to form graphene aerogel (GA), and sodium ions and ferrocyanide ions react to generate Na 3.1 Fe 4 [Fe(CN) 6 ] 3 , get Na 3.1 Fe 4 [Fe(CN) 6 ] 3 @GA composite material, which can be directly pressed into the positive electrode.
[0064] The preparation method provided by the present invention adopts two thermal reactions to prepare hydrogel, and then freeze-drying to prepare aerogel composite materials with a three-dimensional spatial network structure. In the first thermal reaction, the composite material is basically generated in the reaction system; in the second thermal reaction, the reaction products in the system condense into blocks, the volume is reduced, the density is increased, and the structural stability of the composite material is improved. The present invention can not only ensure the stability of the three-dimensional spatial structure of the composite material through the two-step thermal reaction method, but also ensure that the Na generated by the reaction 3.1 Fe 4 [Fe(CN) 6 ] 3 Nanomaterials are defect-free and amorphous, and their use as electrode materials will not cause battery capacity decay or poor cycle performance.
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a self-supporting positive electrode material, It is characterized in that include: The reaction slurry is placed in an environment of 65-75° C. to react for 20-28 hours, and then the temperature is raised to 90-110° C. to react for 2-3 hours to obtain a hydrogel, and the hydrogel is freeze-dried to obtain a self-supporting positive electrode material; The components of the reaction slurry include deionized water, graphene oxide, a reducing agent for reducing the graphene oxide, and a reducing agent for reacting to generate Na 3.1 Fe 4 [Fe(CN) 6 ] 3 of ferrocyanide and sodium ions; The graphene oxide reacts with the target Na 3.1 Fe 4 [Fe(CN) 6 ] 3 The molar ratio is 1:0.9~1.
1.
2. The preparation method according to claim 1, It is characterized in that The preparation method of the reaction slurry comprises: Sodium ferrocyanide, reducing agent, graphene oxide powder and deionized water were mixed and ultrasonically dispersed for 50 to 70 minutes.
3. The preparation method according to claim 2, It is characterized in that The reaction slurry also includes ethylene glycol, the volume ratio of the deionized water to the ethylene glycol is 0.8-1.2:1, and the volume ratio of the graphene oxide powder to the ethylene glycol is 1 mol:1.5-1.8L.
4. The preparation method according to claim 2, It is characterized in that Also includes at least one of the following features (1) and (2): (1) The sodium ferrocyanide is Na 4 Fe(CN) 6 10H 2 O; (2) The particle size of the graphene oxide powder is 50-500 nm.
5. The preparation method according to claim 1, It is characterized in that The reducing agent is selected from at least one of ethylenediamine and ascorbic acid.
6. The preparation method according to claim 1, It is characterized in that Before freeze-drying the hydrogel, impurities are removed by washing the hydrogel alternately with deionized water and anhydrous ethanol for multiple times.
7. A self-supporting cathode material, It is characterized in that The method is prepared according to any one of claims 1 to 6.
8. A method for preparing a positive electrode, It is characterized in that The method comprises pressing the self-supporting positive electrode material as claimed in claim 7 into sheets.
9. A positive electrode, It is characterized in that The method is prepared according to claim 8.
10. A battery, It is characterized in that Comprising the positive electrode as claimed in claim 9.
